Regulation by Light of Chemotaxis to Nitrite during the Sexual Life Cycle in Chlamydomonas reinhardtii - Ermilova, Elena (Plants (Basel), 2014)
Nitrite plays an important role in the nitrogen metabolism of most cells, including Chlamydomonas reinhardtii. We have shown that vegetative cells of C. reinhardtii are attracted by nitrite. The Nia1nit2 mutant with defects in genes encoding the nitrate reductase and regulatory protein NIT2 respectively was found to exhibit normal chemotaxis to nitrite. The data suggest that chemotaxis events appear to be specific and independent of those involved in nitrate assimilation. Unlike vegetative cells and noncompetent pregametes, mature gametes did not show chemotaxis to nitrite. Just like gamete formation, the change in chemotaxis mode is controlled by the sequential action of two environmental cues, removal of nitrogen from the medium and light. Comparative analysis of wild-type and RNAi strains with reduced level of phototropin has indicated that switch-off of chemotaxis towards nitrite is dependent on phototropin. The studies revealed individual elements of the phototropin-dependent signal transduction pathway involved in the blue-light-controlled change in chemotaxis mode of C. reinhardtii during gamete formation: three protein kinases, one operating against signal flux and two that promote signal transduction. We have proposed a working model for the signaling pathway by which blue light controls chemotaxis towards attractants, which are nitrogen sources, during pregamete-to-gamete conversion of C. reinhardtii.